2010
DOI: 10.1902/jop.2010.090643
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and Microbiologic Profiles of Chronic and Aggressive Periodontitis Subjects

Abstract: There were no statistically significant differences in the measured immunologic and microbiologic parameters between subjects with GCP and GAgP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 35 publications
6
85
1
5
Order By: Relevance
“…www.intechopen.com Rescala et al (2010) reported similar microbiological and immunological parameters for subjects with chronic periodontitis and AgP who showed comparable periodontal disease severity. Herein we report dental management of an otherwise healthy patient diagnosed with generalized AgP and rapidly progressing bone loss throughout the mouth.…”
Section: Treatment Resultsmentioning
confidence: 87%
“…www.intechopen.com Rescala et al (2010) reported similar microbiological and immunological parameters for subjects with chronic periodontitis and AgP who showed comparable periodontal disease severity. Herein we report dental management of an otherwise healthy patient diagnosed with generalized AgP and rapidly progressing bone loss throughout the mouth.…”
Section: Treatment Resultsmentioning
confidence: 87%
“…7 GCF is a complex biological fluid that contains a mixture of serum-derived and inflammatory proteins. 8 The constituents of GCF arise from a variety of sources, including microbial plaque, host cells, and serum-derived factors; thus, a number of biomarkers are available to examine in the GCF. 7,8 Matrix metalloproteinase-9 (MMP-9) is derived predominantly from monocytes and macrophages, and its levels in GCF are higher in patients with periodontitis; therefore, MMP-9 may serve as a biomarker of periodontal disease and aid in early detection of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…8 The constituents of GCF arise from a variety of sources, including microbial plaque, host cells, and serum-derived factors; thus, a number of biomarkers are available to examine in the GCF. 7,8 Matrix metalloproteinase-9 (MMP-9) is derived predominantly from monocytes and macrophages, and its levels in GCF are higher in patients with periodontitis; therefore, MMP-9 may serve as a biomarker of periodontal disease and aid in early detection of periodontitis. 9 An intermediate mechanism that lies between bacterial stimulation and tissue remodeling is the production of cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…The disease could ultimately lead to the formation of periodontal pockets upon bone loss and apical migration of the junctional epithelium [3,4]. It is classified into aggressive periodontitis (AP) and chronic periodontitis (CP) [5,6].…”
Section: Introductionmentioning
confidence: 99%